The Influence of E-Perceived Value, E-Service Quality, and E-Received Risks on E-Loyalty - Romadhoni, Buyung; Akhmad, Akhmad; Mauliana, Deasy (Al-Buhuts, 2024)
The purpose will be to test the influence of perceived value, perceived service quality, and perceived risks on e-loyalty. In this study, a quantitative research approach is used. Quantitative research is research that uses data analysis in the form of numbers. The population that will be taken in this study is all customers who transact at PT Bank Syariah. The population in this study uses an infinite population, where the infinite population in this study is taken from a customer of PT Bank Syariah Indonesia, KCP Makassar Panakukang. The sampling technique used was accidental sampling, so the number of samples was 145 respondents. The data analysis method is multiple linear regression analysis. The results of the study found that perceived value has a significant effect on e-loyalty, service quality has a significant effect on e-loyalty, and perceived risk has a significant effect on e-loyalty.